Defending Homes and Making Banks Pay: California's Home Defenders League - Reese, Ellen (Social justice, 2013)
The article discusses research findings on the efforts of the political organization, the Alliance of Californians for Community Empowerment (ACCE), to organize homeowners against foreclosures in California. Topics include the role of homebuilders and deregulation of large financial institutions in the foreclosure crisis and efforts by the ACCE to seek accountability from banks and improve fair lending policies and legislation.